VO2max, aerobic and anaerobic thresholds in five test modes on treadmill in cross country skiers - Hynynen, E.; Mendia, I.; Monahan, K.; Kyröläinen, H. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Laboratory exercise testing is commonly used to evaluate the physiological capacity and to prescribe individual exercise intensity zones of an endurance athlete. In cross country skiing, numerous different skiing techniques are used in training and differences exist especially between classic and skating styles (Rusko 2003). The purpose of this study was to compare VO2max, Aerobic (AerT) and Anaerobic Threshold (AnT) in Nordic Walking (NW), V1, V2, Diagonal Striding (DS) and Double Poling (DP) techniques.